Metal-ion Binding to Host Defense Peptide Piscidin 3 Observed in Phospholipid Bilayers by Magic Angle Spinning Solid-state NMR - Rai, Ratan Kumar (Chemphyschem, 2018)
Cationic antimicrobial peptides (AMPs) are essential components of the innate immune system. They have attracted interest as novel compounds with the potential to treat infections with multi-drug resistant bacteria. In this study, we investigate piscidin 3 (P3), an AMP that was first discovered in the mast cells of hybrid striped bass. Prior studies have shown that P3 is less active than its homolog piscidin 1 (P1) against planktonic bacteria. However, it has the advantage of being less toxic to mammalian cells and more active on biofilms and persister cells. Both peptides cross bacterial membranes and co-localize with intracellular DNA but P3 is more condensing to DNA while P1 is more membrane active. Recently, we showed that both peptides coordinate Cu(2+) through an amino-terminal copper and nickel (ATCUN) motif. We also demonstrated that the bactericidal effects of P3 are linked to its ability to form radicals that nick DNA in the presence of Cu(2+). Since metal binding and membrane crossing by P3 is biologically important, we apply solid-state NMR spectroscopy to uniformly (13)C-(15)N-labeled peptide samples to structurally characterize the ATCUN motif of P3 bound to bilayer and coordinated to Ni(2+) and Cu(2+). These experiments were supplemented with density functional theory calculations. Taken together these results refine the arrangement of not only the backbone but also side chain atoms of an AMP simultaneously bound to metal ions and phospholipid bilayers.